Effects of Brief Messages About Antiretroviral Therapy and Condom Use Benefits Among Black and Latino MSM in Three U.S. Cities. Issue 2 (28th January 2018) - Herbst, Jeffrey H.; Mansergh, Gordon; Pitts, Nicole; Denson, Damian; Mimiaga, Matthew J.; Holman, Jeremy
ABSTRACT: This pilot study examined effects of HIV prevention messages about self and partner benefits of antiretroviral therapy (ART) and condom effectiveness on increased intentions for behavior change. Data were from Messages4Men, a study examining prevention messages among 320 HIV-positive and 605 HIV-negative Black and Latino MSM. Men completed a computer-based assessment after message exposure, and multivariable models controlled for risky sex and demographics. A majority of HIV-positive men reported increased intentions for ART use; 22% reported partner benefit information was new. HIV-positive men with a detectable viral load had significantly greater adjusted odds of reporting intentions for ART use. Over half of HIV-negative MSM reported ART benefit information was new, and 88% reported increased intentions to discuss ART use with infected partners. Black MSM anticipated they would increase condom use in response to the self and partner benefit messages. Tailored messages on benefits of ART are needed for MSM.